2 William Waller Hening, The Statutes at Large: Being a Collection of all the Laws of Virginia 126 (1823) - (:unkn) unknown (My University, 1662)
"that every man able to beare armes have in his house a fixed gun, two pound of powder and eight pound of shot at least"
Keywords: REQUIRED POSSESSION